2017
DOI: 10.1055/s-0037-1607430
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgical Issues in Pregnancy

Abstract: Although rare, intracranial hemorrhage due to rupture of cerebral vascular malformations or intracranial aneurysms during pregnancy is a potentially devastating and life-threatening disorder, posing a diagnostic and therapeutic challenge to a multidisciplinary team of neurosurgeons, neurologists, obstetricians, and anesthesiologists. Despite the significant risk of morbidity and mortality affecting both the mother and the unborn child, knowledge of the natural history, epidemiology, and appropriate management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…In a multidisciplinary discussion between neurosurgeons and obstetricians, we judged digital subtraction angiography and subsequent embolization as reasonable, considering the deterioration of retrograde leptomeningeal venous drainage due to the increase in cardiac output in the third trimester of a twin pregnancy. 1,2,5 Under the informed consent of the patient for our treatment strategy, we performed the procedure on day 28 2/7 weeks of gestation.…”
Section: History and Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a multidisciplinary discussion between neurosurgeons and obstetricians, we judged digital subtraction angiography and subsequent embolization as reasonable, considering the deterioration of retrograde leptomeningeal venous drainage due to the increase in cardiac output in the third trimester of a twin pregnancy. 1,2,5 Under the informed consent of the patient for our treatment strategy, we performed the procedure on day 28 2/7 weeks of gestation.…”
Section: History and Examinationmentioning
confidence: 99%
“…As to intracranial aneurysms and cerebral arteriovenous malformations, many reports in the literature have discussed how the risk of hemorrhage changes and how to deal with the disease during pregnancy. 1,2 In contrast, less is known about the relationship between pregnancy and dural arteriovenous fistulae (DAVF). Several literature reviews have suggested that pregnancy potentially triggers the formation of DAVF.…”
Section: Introductionmentioning
confidence: 99%
“…However, the unique risks related to pregnancy were not addressed in that trial. Conservative management is usually recommended in the absence of intracranial hemorrhage, although some experts recommend preemptive treatment given the special risks of pregnancy (97). In patients with high-risk features including deep location and drainage, arteriovenous fistula, or concomitant aneurysm, the timing of any planned intervention should be decided on an individualized basis (18).…”
Section: Management Of Hemorrhagic Stroke In Pregnancymentioning
confidence: 99%
“…Delaying interventions or diagnostic testing due to fear of possible radiation or contrast effects has proven to be detrimental for mother and the fetus (56,98). To date, most evidence has shown no increased rupture of cerebral aneurysms during pregnancy, and conservative treatment of unruptured aneurysms is recommended in most cases (97).…”
Section: Management Of Hemorrhagic Stroke In Pregnancymentioning
confidence: 99%
“…However, there are multiple reports of high blood pressure and bleeding from arteriovenous malformations or cerebral aneurysm. [ 4 ] If caesarean delivery is recommended from the outset, spinal anaesthesia appears to suit the objectives of appropriate care, as it avoids risky intubation in pregnancy and allows for good neurological monitoring. [ 2 5 ] Coagulation must be carefully monitored during the entire process, as it could be a risk factor for cerebral bleeding.…”
mentioning
confidence: 99%